Adrenal suppression from glucocorticoids: preventing an iatrogenic cause of morbidity and mortality in children - Alexandra Ahmet; Arati Mokashi; Ellen B Goldbloom; Celine Huot; Roman Jurencak; Preetha Krishnamoorthy; Anne Rowan-Legg; Harold Kim; Larry Pancer; Tom Kovesi (BMJ Publishing Group, 2019)
Adrenal suppression (AS) is an important side effect of glucocorticoids (GCs) including inhaled corticosteroids (ICS). AS can often be asymptomatic or associated with non-specific symptoms until a physiological stress such as an illness precipitates an adrenal crisis. Morbidity and death associated with adrenal crisis is preventable but continues to be reported in children. There is a lack of consensus about the management of children at risk of AS. However, healthcare professionals need to develop an awareness and approach to keep these children safe. In this article, current knowledge of the risk factors, diagnosis and management of AS are reviewed while drawing attention to knowledge gaps and areas of controversy. Possible strategies to reduce the morbidity associated with this iatrogenic condition are provided for healthcare professionals.